Protective role of Pomegranate (punica granatam L.) juice in inhibition liver toxicity induced by amikacin in white Newzealad Rabbits - Dakheel Hussein Hadree (Tikrit Journal of Pure Science)
In present study, aminoglycosides as amikacin, was proved to induce alterations in the liver of experimental animals. The aim present study is to investigate the effect of amikacin  on rabbit liver which is commonly used in infections resistant to other antibiotics and study treated and protective effect of Pomegranate juice(Punica granatum L.), which antibiotic inhibit & decrease liver toxic formed by amikacin in males and females white rabbits by measuring some of the criteria for biochemical variations, such as, blood serum cholesterol (Ch), triglyceride concentration (TG), blood serum high density lipoprotein-cholesterol (HDL-C),Low density lipoprotein-cholesterol (LDL-C) concentration. In those were given (amikacin80mg/kg) by injection in muscle for period  of 15 days, caused a significant increase at the level (p≤0.05) in cholesterol(Ch), triglyceride(TG) concentration, Low density lipoprotein-cholesterol concentration(LDL-C) as compared with a control group, while decreased concentration of high density lipoprotein-cholesterol(HDL-C) significantly as compared with the control group. The rabbits treated with Pomegranate juice 100ml the concentration of 40% for a period of 15 days has recorded a significant decrease in the concentrations of cholesterol, triglyceride concentration and low density lipoprotein-cholesterol concentration as compared with a group Rabbits treated with amikacin only, and increased significantly in high density lipoprotein-cholesterol compared to the group treated with amikacin  only